(untitled) (Transport systems and technologies, 2022)
The seaworthiness includes the conformity of the parameters of the vessel’s stability and strength to the permissible limits, which is provided during the port loading and discharging operations. Requirements concerning the ship’s stability and strength are universal for all types of vessels and are postulated in the International Maritime Organization (IMO) codes and documents of the shipping registers of different countries. The cargo operations of bulk carriers are responsible moment, as it determines the level of their seaworthiness and maritime safety at the sea voyage. For bulkers raised strict requirements in regard of cargo distribution and ballast operations with continuous control of their stability and strength. The search of methods for optimal performing cargo operations of the bulk vessels with assurance of all seaworthy parameters at the safe level remains actual. The bulk carriers usually have instructions for their standard loading options provided by the ship’s builder, the character of which depends on the specific cargo volume and the number of holds processed at the same time. For each standard variant of cargo operations, the instructions provide a sequence of stages of loading the vessel. At the end of each stage, the vessel must be in acceptable seaworthy condition. In the situation of non-standard loading of bulk carriers, which are not covered by the shipbuilder’s instructions, there are difficulties with planning and conducting cargo operations to ensure proper seaworthiness of the vessel, efficient use of its carrying capacity. Ship personnel must independently deal with the distribution of cargo, sorting through various loading options, which is not always efficient and time consuming. At the same time, a number of restrictions on the seaworthiness of the vessel must be met. The purpose of this article is to analyze the possibilities of determining acceptable variants of loading of the bulk vessel, which satisfy the limitations imposed by parameters of the seaworthiness and marine safety. The limitations imposed by the requirements of continuous vessel’s seaworthiness were considered and divided into groups with a view to creating an optimization task. The general approach to formation of a number of permissible loading of the bulk vessel, proposed in the article, creates preconditions for setting the task of choosing the optimal strategy of carrying out cargo operations on the criteria of continuous observance of seaworthy characteristics of the vessel.